2002
DOI: 10.1002/prot.10095
|View full text |Cite
|
Sign up to set email alerts
|

Conformational polymorphism of wild‐type and mutant prion proteins: Energy landscape analysis

Abstract: Conformational transitions are thought to be the prime mechanism of prion diseases. In this study, the energy landscapes of a wild-type prion protein (PrP) and the D178N and E200K mutant proteins were mapped, enabling the characterization of the normal isoforms (PrP(C)) and partially unfolded isoforms (PrP(PU)) of the three prion protein analogs. It was found that the three energy landscapes differ in three respects: (i) the relative stability of the PrP(C) and the PrP(PU) states, (ii) the transition pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…So far, our knowledge of PrP Sc characteristics in gCJD originates from studies using brain material. Accordingly, in E200K or V210I mutation carriers, the disease is caused by an altered structure of PrP C [ 19 ] and the metabolism of PrP is different during life [ 20 ]. These conformational changes might engender its conversion into PrP Sc by affecting the interactions with other cellular partners or the fibrillation process of PrP [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…So far, our knowledge of PrP Sc characteristics in gCJD originates from studies using brain material. Accordingly, in E200K or V210I mutation carriers, the disease is caused by an altered structure of PrP C [ 19 ] and the metabolism of PrP is different during life [ 20 ]. These conformational changes might engender its conversion into PrP Sc by affecting the interactions with other cellular partners or the fibrillation process of PrP [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous conformational studies indicate that a transition from α-helical to β-sheet structures (PrP C PrP Sc ) is likely to be the crucial event in prion propagation [31,32,33,34,35]. To investigate which portions of the native protein sequence are involved in the conformational transition from PrP C to PrP Sc and PrP amyloid, several groups have analyzed the secondary structures and fibrillogenic properties of synthetic PrP peptides [36].…”
Section: Introductionmentioning
confidence: 99%
“…However, the dynamic details of structural transition need novel methods to probe the solution state structure of prion peptide fragments using spectroscopic techniques. Early conforma-tional studies have indicated that a transition from a-helical to b-sheet structure (PrP c -PrP Sc ) is likely to be the crucial event in prion propagation (Pan et al, 1993;Prusiner, 1998;Prusiner et al, 1998;Petchanikow et al, 2001;Levy and Becker, 2002). To investigate which amino acid sequences feature in the conformational transition from PrP c to PrP Sc and PrP amyloid, several groups have analyzed the secondary structure and fibrillogenic properties of synthetic peptides of PrP (Baldwin et al, 1995).…”
Section: Introductionmentioning
confidence: 99%